2016
DOI: 10.1007/s11302-016-9553-0
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes during human P2X7 receptor activation examined by structural modelling and cysteine-based cross-linking studies

Abstract: The P2X7 receptor (P2X7R) is important in mediating a range of physiological functions and pathologies associated with tissue damage and inflammation and represents an attractive therapeutic target. However, in terms of their structure-function relationships, the mammalian P2X7Rs remain poorly characterised compared to some of their other P2XR counterparts. In this study, combining cysteine-based cross-linking and whole-cell patch-clamp recording, we examined six pairs of residues (A44/I331, D48/I331, I58/F311… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the case of P2X7, alanine A44 could form hydrophobic interaction with isoleucine I331, which cysteine substitution, I331C, has been shown to exhibit a delayed deactivation time course (Pippel et al, 2017); the distances are 4.0 Å and 10.6 Å in the closed and open states, respectively (Figure 8d). However, application of DTT to the doubly mutated receptor A44C/I331C did not increase the agonist‐induced current (Caseley et al, 2017). It has been suggested that A44 is nestled more deeply in the TM1 domain and is not well positioned toward I331 to form a disulfide bond (Caseley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of P2X7, alanine A44 could form hydrophobic interaction with isoleucine I331, which cysteine substitution, I331C, has been shown to exhibit a delayed deactivation time course (Pippel et al, 2017); the distances are 4.0 Å and 10.6 Å in the closed and open states, respectively (Figure 8d). However, application of DTT to the doubly mutated receptor A44C/I331C did not increase the agonist‐induced current (Caseley et al, 2017). It has been suggested that A44 is nestled more deeply in the TM1 domain and is not well positioned toward I331 to form a disulfide bond (Caseley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, application of DTT to the doubly mutated receptor A44C/I331C did not increase the agonist‐induced current (Caseley et al, 2017). It has been suggested that A44 is nestled more deeply in the TM1 domain and is not well positioned toward I331 to form a disulfide bond (Caseley et al, 2017). Thus, the role of A44 in P2X7 sensitization and dye uptake remains to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Since PDI inhibits N -methyl- d -aspartate receptor (NMDAR) activity via sulfhydration (reduction) of disulfide bonds [ 7 , 22 ], it is plausible that the L-NAME would also attenuate microglial activation and DG astroglial apoptosis by facilitating PDI-mediated reduction of surface P2X7R. However, P2X7R-mediated currents are unaffected by the reduction of disulfide bonds on surface P2X7R [ 47 ]. Therefore, our findings suggest that PDI-mediated S -nitrosylation of P2X7R may reinforce SE-induced microglial activation and DG astroglial loss by increasing its surface expression, independent of activities of PDI and surface P2X7R.…”
Section: Discussionmentioning
confidence: 99%
“…While the structures reveal that the upper body remains overall relatively immobile, there is increasing functional evidence to support that conformational changes occur in the upper body during P2X7 receptor activation. Simultaneous cysteine substitutions of Lys 81 and Val 304 in the human P2X7 receptor hindered receptor activation that was reversed by treatment with the reducing agent dithiothreitol (DTT) [48], indicating that these two residues or positions are in close vicinity in the closed state and move apart distantly in the open state. Replacement of Val 87 in the human P2X7 receptor with the corresponding isoleucine in the rat P2X7 receptor enhanced current responses to ATP and BzATP [49], suggesting that residue at this position influences the local conformational change differently in the rat and human receptors.…”
Section: Agonist-induced Conformational Changes In the Extracellular And Transmembrane Domainsmentioning
confidence: 99%
“…3d ). In the human P2X7 receptor, simultaneous introduction of cysteine substitution at Asp 48 and Ile 331 , located in the extracellular end of the TM1 and TM2 α-helices, respectively, prevented receptor activation, which was rescued by treatment with DTT [ 48 ]. Thus, these two residues or positions are in close proximity in the closed state and distance significantly from each other in the open state, supporting occurrence of considerable conformational changes in the external vestibule.…”
Section: The Transmembrane Ion-permeating Pathwaymentioning
confidence: 99%